Oral Health Management of Pregnant Dental Patients - Rose Geist (Association of American Medical Colleges, 2009)
Abstract This module from the Clinical Manual at the University of Detroit Mercy School of Dentistry guides students in the treatment of medically complex patients. There has been much confusion among students and clinical instructors regarding oral health care procedures for pregnant patients. Uncertainty about what can and cannot be done for these patients has led to incorrect clinical decisions; some patients have been dismissed from the clinic with no care provided. Lack of supporting evidence underlies much of this confusion. This resource provides current evidence to facilitate clinical decisions based on the principles of evidence-based dentistry. It also helps develop communication skills between obstetricians and oral health care providers, permitting them to share health information about the patient and fetus. The material was created based on requests of students and faculty for guidance in managing pregnant dental patients. Since this material has been available, much confusion has been resolved and patients receive appropriate care based on scientific evidence. Clinical instruction should be based on current evidence and comprehensive assessment of the patient, involving both medical consultation and patient values. Through using these guidelines, students are more confident in decision-making when treating pregnant patients.